Biodegradable PLGA nanoparticles loaded with hydrophobic drugs: confocal Raman microspectroscopic characterization1. Issue 18 (14th May 2015) - Yan, Hu; Hou, Yi-Fan; Niu, Peng-Fei; Zhang, Ke; Shoji, Tatsuya; Tsuboi, Yasuyuki; Yao, Fang-Yao; Zhao, Li-Min; Chang, Jun-Biao
<x xml:space="preserve">Abstract</x> PLGA nanoparticles with bicyclol and Br-NBP were for the first time successfully characterized by a laser trapping/confocal Raman spectroscopic technique only using individual nanoparticles.